Analysis of cross-protection between serotypes and passively transferred immune globulin in experimental nutritionally variant streptococcal endocarditis. - van de Rijn, I (1988)
Nutritionally variant streptococci (NVS), which account for 5 to 10% of all cases of streptococcal endocarditis, were recently subdivided into three serotypes. In the past, using a rabbit endocarditis model, I demonstrated that by immunization of rabbits with NVS and by challenge with a strain from the homologous serotype a level of 90 to 100% protection was elicited. In the present study, the level of cross-protection between strains from different serotypes was measured. No cross-protection was demonstrated between serotype I and II or III strains. However, significant cross-protection was observed when serotype II and III strains were analyzed in the model. Since high levels of immunoglobulin G were demonstrated against the surface of the NVS after immunization, passive transfer experiments were initiated. Even at comparable levels of surface immunoglobulin G, none of the rabbits given immune globulin were protected against challenge with a dose of live NVS that equaled 20 times the 50% infective dose. Therefore, it appears that components from the immune system, in addition to humoral components, are required for active protection against NVS endocarditis.